Phenotypic and molecular identification of Brucella suis biotype 1 in a pig from Brazil—case report - Vicente, Acácia Ferreira; Mioni, Mateus de Souza Ribeiro; Cagnini, Didier Quevedo; Ribeiro, Márcio Garcia; Arabe Filho, Marcelo Fagali; Listoni, Fernando José Paganini; Ribeiro, Bruna Letícia Devidé; Megid, Jane (Springer Nature, 2022)
Brucellosis is a zoonotic disease with a global impact. Brucellasuis is one of the most pathogenic species to humans, requiring different measures for the control and/or eradication of the disease. The serological investigation for brucellosis was performed in pigs, horses, dogs, and cattle on a farm with a history of abortion in sows and necropsy of a boar with severe necrosuppurative orchitis. One sow, two cows, and two dogs reveled positive to Rose Bengal Test (RBT), although only the sow had a confirmatory outcome in 2-mercaptoethanol (2-ME). The 2-ME-positive sow was euthanized and microbiological culture of lymph nodes and liver followed by biochemical characterization allowed phenotypic characterization of Brucellasuis biotype 1. PCR multiplex Bruce-ladder and Suis-ladder enabled molecular confirmation, respectively, of Brucellasuis and biotype 1. The transmission aspects of B.suis to pigs and other domestic species, the combination of diagnostic procedures to diagnosis, as well as human health concerns of brucellosis are discussed.
Keywords: Brucellosis; Human exposure; PCR; Serodiagnosis; Swine; Zoonosis